Severe trauma leads to sustained muscle loss, induced frailty, and distinct temporal changes in myokine and chemokine profiles of older patients - Polcz, Valerie E.; Barrios, Evan L.; Cox, Michael C.; Rocha, Ivanna; Liang, Muxuan; Hawkins, Russell B.; Darden, Dijoia; Ungaro, Ricardo; Dirain, Marvin; Mankowski, Robert; Mohr, Alicia M.; Moore, Frederick A.; et al. (Surgery, 2024)
Sarcopenia is a known risk factor for adverse outcomes across multiple disease states, including severe trauma. Factors such as age, hyperinflammation, prolonged immobilization, and critical illness may not only exacerbate progression of this disease but may also contribute to the development of induced sarcopenia, or sarcopenia secondary to hospitalization. This study seeks to (1) determine the effects of severe traumatic injury on changes in skeletal muscle mass in older adults; (2) test whether changes in skeletal muscle mass are associated with clinical frailty, physical performance, and health-related quality of life; and (3) examine trauma-induced frailty and temporal changes in myokine and chemokine profiles. A prospective, longitudinal cohort study of 47 critically ill, older (≥45 years) adults presenting after severe blunt trauma was conducted. Repeated measures of computed tomography–based skeletal muscle index, frailty, and quality of life were obtained in addition to selected plasma biomarkers over 6 months. Severe trauma was associated with significant losses in skeletal muscle mass and increased incidence of sarcopenia from 36% at baseline to 60% at 6 months. Severe trauma also was associated with a transient worsening of induced frailty and reduced quality of life irrespective of sarcopenia status, which returned to baseline by 6 months after injury. Admission biomarker levels were not associated with skeletal muscle index at the time points studied but demonstrated distinct temporal changes across our entire cohort. Severe blunt trauma in older adults is associated with increased incidence of induced sarcopenia and reversible induced frailty. Despite muscle wasting, functional decline is transient, with a return to baseline by 6 months, suggesting a need for holistic definitions of sarcopenia and further investigation into long-term functional outcomes in this population.